DAMPAK PERIKLANAN TERHADAP MINAT BELI PADA HP SAMSUNG GALAXY ( STUDI EKSPLORASI PENGGUNA HP SAMSUNG GALAXY DI SEMARANG ) - Hanik Mufarihah; Triyono - (Universitas Muhammadiyah Semarang, 2013)
The purpose of this research is to determine the influence of advertising on buyer interest of Samsung Galaxy cell phone user in Semarang. Knowing and analyzing what factor of the message in the advertisement, the model of the advertisement, and the frequency of the advertisement broadcast on the television can influence the buying interest of Samsung Galaxy cell phone users. This research also determines which factor that has big influence on buying interest of Samsung Galaxy cell phone user. The populations of the research are the user of Samsung Galaxy cell phone in Semarang city. The data for the research are taken by interviews with the respondents. There are 15 respondents whose the background of education are Junior high, Senior high, Diploma/ Scholar degree. There 5 persons from junior high background, 5 persons from senior high background, and the last are 5 persons from the Diploma/ Scholar degree background. Besides that, there are also some addition data from observations and documentations. The analysis of the data is using data reduction technique, data serving, and concluding. The result of the research is based on the respondent’s responses on questions of the interview. the conclusion of the interview are messages, model, and frequency of the advertisement have the influence on buying interest of Samsung Galaxy cell phone user in Semarang city. Based on the analysis result which can be seen from the education background, message in the advertisement had influence the buying interest from the background education of junior high, Senior high, and Diploma/ Scholar. The model factor of the advertisement which can be seen from the education background had the influence the buying interest of junior high and senior high users. And the factor of broadcast frequency on television had dominant influenced the buying interest among students. From those three factors, the message in the advertisement was the most factor which has great influence of the buying interest of Samsung Galaxy cell phone users on the entire of respondents from education background of Junior high, Senior high, and Diploma/ Scholar degree users.